The contribution of the endothelium to the development of coagulation disorders that characterize Ebola hemorrhagic fever in primates - Hensley, Lisa E.; Geisbert, Thomas W. (Thrombosis and Haemostasis, 2005)
Recently, there have been substantdevelopments ial in the understanding of Ebola hemorrhagic fever pathogenesis, but there are still major gaps. These infections occur in underdeveloped areas of the world,and much of our knowledge of naturally occurring disease is derived from sporadic outbreaks that occurred decades in the past. Recently conducted laboratory animal studies have provided insight into Ebola pathogenesis and may help guide clinical investigations of disease using contemporary methodologies that were not available previously. A better understanding of the relevant host and viral factors that influence clinical and virologic outcome will be critical to our ability to combat this aggressive pathogen. This article reviews the most relevant information relating to the postulated pathogenesis of this disease, focusing on the role of the endothelium in contributing to the coagulation disorders that characterize Ebola hemorrhagic fever in primates. Some of the remaining and key unanswered questions relating to the role of the vascular system in the pathogenesis of this disease, that need to be addressed in further research, are highlighted.
Keywords: Ebola virus; filovirus; hemorrhagic fever; pathogenesis